Iowa Birdline update, June 13, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for June 13, 1994. Highlights include Purple Gallinule, Sandhill Crane, Prairie Warbler, Western Grebe and Least Tern. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed